Management of Sweet Potato Weevil Cylas formicarius (Fab.) - D., Anitha Kumari; V., Suresh; M., Hanuman Nayak; G., Anitha; Hirur, Madhu E. (JOURNAL OF ROOT CROPS, 2020)
Sweet potato is one of the major tuber crops cultivated in Telangana. Sweet potato weevil Cylas formicarius (Fab.) is one of the major constraints in its production. The present study was conducted under All India Coordinated Research Project on Tuber Crops at Vegetable Research Station, Rajendranagar, Sri Konda Laxman Telangana State Horticultural University, during the year 2016-17 and 2017-18. Among the different treatments evaluated for the management of SPW, installation of pheromone traps @ one per 100 m2 was found to be the best treatment in the management of SPW with lowest number of weevils in the collar region at 30 days (0.45) which increased during later period of 60 days (0.90), 90 days (1.40) compared to the other treatments. This treatment resulted in very good marketable yield of 14.20 t ha-1 compared to the total yield of 16.09 t ha-1 indicating better management of SPW with use of pheromones.